BAHASA BAPTISAN DAN DOKTRIN TRITUNGGAL:: ANALISIS TEOLOGIS-NORMATIF ATAS MATIUS 28:19 - Yonathan, Rano (STT-RAI Batam, 2026)
Baptism is an essential liturgical practice in the life of the Christian church that functions not merely as a ritual but also conveys theological meaning as an expression of the church’s confession of faith. In contemporary practice, the use of the phrase “God in each of the persons of the Triune God” in baptism raises theological concerns, particularly regarding its conformity to the witness of Scripture and the doctrine of the Trinity. Therefore, examining baptismal language is necessary to ensure that such practice remains consistent with the foundations of the Christian faith. This study aims to examine the theological meaning of baptismal language in light of the doctrine of the Trinity and to evaluate its implications for the church’s liturgical practice. The research employs a qualitative approach with a normative-theological method through literature study of relevant biblical and systematic theological sources, with particular emphasis on the Gospel of Matthew 28:19 as the biblical foundation of the baptismal formula. The novelty of this research lies in its integrative approach, which positions baptismal language as a locus theologicus that connects scriptural witness, Trinitarian doctrinal reflection, and the evaluation of liturgical praxis within a coherent normative-theological framework. The findings demonstrate that the baptismal mandate in Matthew 28:19 affirms the one name of God revealed in the relational identity of the Father, the Son, and the Holy Spirit. However, the expression “God in each person” may lead to theological ambiguity if it is not understood within the unity of the Triune God. Therefore, baptismal language must be formulated carefully in a theological and conceptual manner in order to remain faithful to Trinitarian doctrine and to properly shape the theological understanding of the congregation.